Rwanda : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
As explained in IMF Country Report No. 20/115, COVID-19 has had a severe economic impact on Rwanda through the implementation of strict domestic measures to contain the spread of the virus and related global spillovers. The authorities have responded by deploying health and economic measures totaling USD 311 million (3.3 percent of GDP). They have also set up an economic recovery fund to support firms affected by the pandemic. To help address the urgent balance of payments (BOP) need arising from the pandemic, currently estimated at about USD 433 million, the authorities request an additional disbursement under the Rapid Credit Facility (RCF) of 50 percent of quota (SDR 80.1 million) under the 'exogenous shock' window of the RCF. This follows the Executive Board's approval on April 2, 2020 of the authorities' earlier request for the same amount, before the doubling of the annual access limit of emergency financing under the 'exogenous shock' window of the RCF to 100 percent of quota on April 9, 2020. This additional request will bring the total disbursement under the RCF to 100 percent of quota.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet